2007
DOI: 10.1007/s11095-007-9303-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell Penetrating Peptides: Intracellular Pathways and Pharmaceutical Perspectives

Abstract: Cell penetrating peptides, generally categorized as amphipathic or cationic depending on their sequence, are increasingly drawing attention as a non-invasive delivery technology for macromolecules. Delivery of a diverse set of cargo in terms of size and nature ranging from small molecules to particulate cargo has been attempted using different types of cell penetrating peptides (CPPs) in vitro and in vivo. However, the internalization mechanism of CPPs is an unresolved issue to date, with dramatic changes in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
346
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(355 citation statements)
references
References 142 publications
(253 reference statements)
2
346
0
7
Order By: Relevance
“…Previous detailed biophysical characterization of the structure and interactions of PTDs within membranes allowed important insights into the energetics of peptide translocation and the mechanisms of penetration processes (20,30,31). An especially well-studied PTD is the TAT peptide, and its cell penetrating capabilities have been characterized in detail (10 Numerous studies exist on the structures, which are adopted by PTDs in solution and in membranes, but not much is known about their mobility on or within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous detailed biophysical characterization of the structure and interactions of PTDs within membranes allowed important insights into the energetics of peptide translocation and the mechanisms of penetration processes (20,30,31). An especially well-studied PTD is the TAT peptide, and its cell penetrating capabilities have been characterized in detail (10 Numerous studies exist on the structures, which are adopted by PTDs in solution and in membranes, but not much is known about their mobility on or within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of CPPs to efficiently deliver cargo is dependent on the cellular association of the CPP to the target cell and the mechanism by which the CPP/cargo is transported into the cell. The mechanism of membrane translocation of CPPs and cargo, however, has yet to be identified definitively (Zorko and Langel 2005;Patel, Zaro et al 2007) and there are conflicting studies regarding whether the CPP internalization mechanism involves energy-dependent endocytosis or a non-endocytic mechanism (Drin, Cottin et al 2003;Richard, Melikov et al 2003;Ziegler, Nervi et al 2005). Despite the fact that different CPPs internalize into cells through different mechanisms (i.e., endocytosis or energy-independent membrane perturbations), recent observations have indicated that internalization of these CPPs occurs via endocytosis when the CPPs are coupled with high molecular weight cargo (Console, Marty et al 2003;Lundberg, Wikstrom et al 2003).…”
Section: Dicussionsmentioning
confidence: 99%
“…Amphipathic CPPs have a hydrophilic face, which consists mostly of lysine residues (22). The presence of amphipathic helixes with hydrophilic and hydrophobic faces is considered as an essential structural requirement for these peptides to cross the plasma membrane at neutral pH (23).…”
Section: Classes Of Cppsmentioning
confidence: 99%
“…It has also been suggested that CPP transduction occurs through a direct internalization or concurrently through nonspecific endocytosis (22) or that CPPs mainly translocate across the cell membranes in a receptor-and energy-independent manner (42). The direct transfer of CPPs may also be accomplished by changes in transmembrane potential and through the formation of inverted micelles (6,43).…”
Section: Mode Of Traffickingmentioning
confidence: 99%
See 1 more Smart Citation